Pencarian Bahan Aktif Antimalaria Daun Bunga Matahari (Helianthus annuus L.) Terhadap Plasmodium falciparum - Nuriha Marangoh, - (2021)
Malaria is an infectious disease caused by the parasitic protozoan genus Plasmodium which is transmitted by female Anopheles mosquito bites. Sunflower Plant (Helianthus annuus L.) comes from the Asteracea family. In the previous study it was reported that the leaves extract of H. annus L possesed antimalarial activity. To find out the potency of H. annuus L. plant as an antimalarial drug, a series of tests is needed to obtain quality, safe, and effective results. The aims of the current study are to investigate the antimalarial activity of various H. annuus extracts, to determine the toxicity as well as to identify compounds in the active fractions. Extraction was carried out by maceration with n-hexane, chloroform and ethanol 96% in order of increasing polarity. Fractionation was conducted by vacuum liquid chromatography, while subfractionation was done by preparative TLC. The antimalarial activity was carried out against Plasmodium falciparum strain 3D7 in vitro. The toxicity tests using the MTT method by using Huh7it cells. The selectivity index (SI) was calculated based on ratio of CC50 / IC50. The results of antimalarial assay showed that chloroform extract had an IC50 value of 0.006 μg / mL and CC50 of> 100 μg / mL, ethanol 96% extract had an IC50 value of 0.02 μg / mL and CC50> 100 μg / mL, and n-hexane extract had IC50value 1.12 μg / mL and CC50> 100 μg / mL. Based on these results it can be concluded that the chloroform extract of H. annuus L. leaves inhibits P. falciparum strain 3D7 at the highest IC50 value of 0.006 μg / mL and shows low toxicity with CC50 value of> 100 μg / mL. Fractionation by VLC of the chloroform extract gave 15 fractions, the based antimalarial screening, fraction F7 showed the highest %inhibition against P. falciparum 85.79%. Further fractionation of F7 by preparative TLC obtained 4 subfractions. Identification of subfraction FF2 was carried out with 1H NMR and LC-MS/MS spectroscopies. The data indicated the presence of Linoelaidic acid and Methyl linoleate.